Postawy elit politycznych Europy Środkowej wobec integracji z UE w okresie przedakcesyjnym - Prażuch, Wojciech (Rocznik Integracji Europejskiej, 2015)
This analysis reviews pro-European and anti-European attitudes in the political life of Visegrad Group states in 1989–2004. It was not easy to identify these attitudes, as the profile of Central European political parties often depended on the personalities of their most prominent persons and their political platforms, especially during the first period of the post-communist era, and these did not keep pace with the changes that occurred around them. In the first half of the decade, integration with the EC/EU was considered an issue related to foreign policy. This was conducive to maintaining a superficial consensus on the matter. As negotiations went into more detail and their finalisation came closer, the political scene became more strongly diversified into three main orientations: „pro-European”, „anti-European” and „Eurosceptic” – based on disputes concerning internal reforms and the pace of these reforms, membership conditions, relations with other European countries or the target integration model. Both pro-European and anti-European discourses were based to a certain extent on emotional arguments, and this did not lead to deeper debates on issues related to integration.